For lidt ordbog og for meget teknik i tekniske oversættelsesordbøger - Leroyer, Patrick (Nordiske Studier i Leksikografi, 2003)
Translators do not translate terminologies, they translate texts. Therefore, they also need textual information about how professional discourses are realised. Unfortunately, technical dictionaries have traditionaly been conceptualised in conformity with the cognitive terminological approach, and very little space has been allocated for textual representation. Such dictionaries are merely systematized lists of technical words and lack any functional lexicographic quality. The lexicographic solution described in this paper is dedicated to satisfy textual information needs. It is realized by the new lexicographic category of textual examples, which supports three different lexicographic data types: translational, thematic and syntactic. First, the theoretical background of the new category will be outlined, and a number of metalexicographic theses will be refuted. A new lexicographic typology will then be introduced, including two models for genre representation in specialized dictionaries. The method of integration will be illustrated in the context of structural and functional dictionary integration. Finally, a number of new lexicographic rules will be established for the different lexicographic tasks: compilation of corpus, selection criteria and validation, lemmatization, treatment of collocation, article configuration, and distributional integration in and outside the macrostructrure.